Math, asked by Aimesh, 1 year ago

(x+y)2-3x-3y+2 factorise

Answers

Answered by MarkAsBrainliest
53
Answer: \\ \\ Now, \\ \\ {(x + y)}^{2} - 3x - 3y + 2 \\ \\ = {(x + y)}^{2} - 3(x + y) + 2 \\ \\ = {(x + y)}^{2} -(x + y) - 2(x + y) + 2 \\ \\ = (x + y)(x + y - 1) - 2(x + y - 1) \\ \\ = (x + y - 1)(x + y - 2), \\ \\ which \: \: is \: \: the \: \: required \\ factorization.

#MarkAsBrainliest

Aimesh: ♥♥♥♥♥♥
Aimesh: ok
Aimesh: (-:
Answered by kedassiri21
11

Answer:

hope u got the answer

plzz mark as brainlist answer

Attachments:
Similar questions